Webster's New World dictionary of the American language - Guralnik, David Bernard 1920-. (Cleveland Collins World, 1976)
A dictionary specially prepared for students containing more than 108,000 vocabulary entries including contemporary slang and informal expressions.
Reprinted under authority of Presidential Decree No. 285 as amended by P.D. Nos. 400 and 1203.
Keywords: Americanisms; English language -- Dictionaries